Inequality and Spatial Convergence in the Mexico City Metropolitan Area, 1989-2010 - Quintana-Romero, Luis; Prudencio-Vázquez, Jaime A.; Salas Páez, Carlos (Journal of Reviews on Global Economics, 2016)
The analysis of inequality and polarization patterns between by regions of a national economy is central to ascertain their possibilities of future economic development. In this work we study such patterns in municipalities and boroughs of Mexico City Metropolitan Area (Zona Metropolitana de la Ciudad de Mexico, ZMCM). The evolution of inequality and polarization in this important area of Mexico is studied with new proposals of measurement using spatially conditioned indexes and through a dynamic transition analysis. The results confirm that the territorial inequality has grown among the municipalities and boroughs that integrate the ZMCM. Moreover, this phenomenon coincides with an increase of the polarization characterized by the formation of four subgroups or convergence clubs.